Oxidative Stress-Induced Afterdepolarizations and Protein Kinase C Signaling - Fei, Yu-Dong; Li, Wei; Hou, Jian-Wen; Guo, Kai; Chen, Xiao-Meng; Chen, Yi-He; Wang, Qian; Xu, Xiao-Lei; Wang, Yue-Peng; Li, Yi-Gang (International journal of molecular sciences, 2017)
Background: Hydrogen peroxide (H2O2)-induced oxidative stress has been demonstrated to induce afterdepolarizations and triggered activities in isolated myocytes, but the underlying mechanisms remain not fully understood. We aimed to explore whether protein kinase C (PKC) activation plays an important role in oxidative stress-induced afterdepolarizations. Methods: Action potentials and ion currents of isolated rabbit cardiomyocytes were recorded using the patch clamp technique. H2O2 (1 mM) was perfused to induce oxidative stress and the specific classical PKC inhibitor, Gö 6983 (1 μM), was applied to test the involvement of PKC. Results: H2O2 perfusion prolonged the action potential duration and induced afterdepolarizations. Pretreatment with Gö 6983 prevented the emergence of H2O2-induced afterdepolarizations. Additional application of Gö 6983 with H2O2 effectively suppressed H2O2-induced afterdepolarizations. H2O2 increased the late sodium current (INa,L) (n = 7, p < 0.01) and the L-type calcium current (ICa,L) (n = 5, p < 0.01), which were significantly reversed by Gö 6983 (p < 0.01). H2O2 also increased the transient outward potassium current (Ito) (n = 6, p < 0.05). However, Gö 6983 showed little effect on H2O2-induced enhancement of Ito. Conclusions: H2O2 induced afterdepolarizations via the activation of PKC and the enhancement of ICa,L and INa,L. These results provide evidence of a link between oxidative stress, PKC activation and afterdepolarizations.